Triplex-DNA stabilization by hydralazine and the presence of anti-(triplex DNA) antibodies in patients treated with hydralazine. - Thomas, T J (1995)
Hydralazine is an antihypertensive drug that elicits andti-nuclear antibodies in patients as an adverse effect. We investigated the ability of hydralazine to promote/stabilize the triplex DNA form of poly(dA).2poly(dT). Under conditions of low ionic strength, the polynucleotide melted as a double helix with a melting temperature (Tm) of 55.3 degrees C. Hydralazine destabilized this duplex form by reducing its Tm to 52.5 degrees C. Spermidine (2.5 microM), a natural polyamine, provoked the triplex form of poly(dA)-.2poly(dT) with two melting transitions, Tm1 of 42.8 degrees C corresponding to triplex-->duplex+single-stranded DNA and Tm2 of 65.4 degrees C, corresponding to duplex melting. Triplex DNA thus formed in the presence of spermidine was further stabilized by hydralazine (250 microM) with a Tm1 of 53.6 degrees C. A similar stabilization effect of hydralazine was found on triplex DNA formed in the presence of 5 mM Mg2+. CD spectra revealed conformational perturbations of DNA in the presence of spermidine and hydralazine. These results support the hypothesis that hydralazine is capable of stabilizing unusual forms of DNA. In contrast with the weak immunogenicity of DNA in its right-handed B-DNA conformation, these unusual forms are immunogenic and have the potential to elicit anti-DNA antibodies. To test this possibility, we analysed sera from a panel of 25 hydralazine-treated patients for anti-(triplex DNA) antibodies using an ELISA. Our results showed that 72% of sera from hydralazine-treated patients contained antibodies reacting toward the triplex DNA. In contrast, there was no significant binding of normal human sera to triplex DNA. Taken together our data indicate that hydralazine and related drugs might exert their action by interacting with DNA and stabilizing higher-order structures such as the triplex DNA.